Factors associated with bleeding events in patients on rivaroxaban for non-valvular atrial fibrillation: A real-world experience. (1st December 2020) - Akhtar, Tauseef; Fratti, Juan Del Cid; Mattumpuram, Jishanth; Fugar, Setri; Uprety, Alok; Nwaichi, Chineme; Torres, Andrea; Mann, Hashim; Golzar, Yasmeen
Abstract: Background: Rivaroxaban is a direct oral anticoagulant (DOAC) approved for the treatment of non-valvular atrial fibrillation (NVAF). Data related to the risk factors associated with rivaroxaban-induced bleeding in patients with NVAF remain scarce in the community setting. We sought to investigate these bleeding risk factors in a racially diverse patient population. Methods: We conducted a single-center, retrospective study based on a chart review of patients who received rivaroxaban from our outpatient pharmacy from January 2015 to April 2018 for NVAF. Any reported bleeding event (BE) was recorded as either major or minor bleeding event. Demographic and clinical data were collected and analyzed. Results: Of the 327 patients included in our analysis, 105 (32%) were female, and the mean age was 62 ± 12 years. Among the included patients, 176 (54%) patients were black, 71 (22%) were white, 51 (15.6%) were Hispanic, 13 (4%) were Asian, and 15 (4.6%) belonged to other races. 89 (27.2%) of the patients had co-prescription of aspirin. A total of 24 (7.3%) patients developed BE, out of which 9 (2.7%) patients had a major BE, and 15 (4.5%) patients had minor BE. Non-fatal gastrointestinal bleeding and epistaxis were the most common type of BE. On multivariable analysis, concurrent aspirin use (81 to 325 mg) (P = 0.03; odds ratio (OR) 2.60 [1.08–6.28]) and increasing age (P = 0.00; OR 1.06 [1.01–1.11]) were independent predictors of BE. Conclusion: In community practice, aspirin co-prescription is common among NVAF patients prescribed rivaroxaban. Increasing age and concurrent aspirin use are independent predictors of BE. Highlights: Aspirin co-prescription is common among NVAF patients prescribed rivaroxaban, in the community. The incidence of reported major bleeding is 2.7%, among NVAF patients prescribed rivaroxaban. Non-fatal GI bleeding and epistaxis are the most commonly reported rivaroxaban-induced BEs. Advanced age and concurrent aspirin use are independent predictors of rivaroxaban-induced BE.